(untitled) (Research, Society and Development, 2025)
Dental implants are a frequent procedure in dental offices, which also makes complications during surgeries common. Therefore, it is crucial that dentists adopt preventive practices to avoid these problems, strictly following the recommended standards. Today, most cases of tooth loss can be treated with implant placement. Understanding the failures is essential to improve the quality of treatments. Continuous improvement of surgical techniques and implant placement is important. This article aims to present an overview of the causes and complications that may arise during implant procedures, with the aim of preventing the occurrence of these problems. A narrative literature review study was conducted. A search was established in the databases of the Regional Portal of the Virtual Health Library (BVS Regional), SciELO, PubMed and Google Scholar, using documents published in the last ten years as search criteria.